PCSK9 Inhibitors in Clinical Practice: Experience of a Specialized Lipid Center - A. V. Blokhina; A. I. Ershova; A. S. Limonova; O. V. Kopylova; A. N. Meshkov; O. M. Drapkina (Рациональная фармакотерапия в кардиологии, 2022)
Aim. To characterize patients receiving PCSK9 inhibitors, and assess the efficiency of their treatment in a specialized lipid center.Material and methods. A retrospective analysis of the medical records of patients who visited the Lipid clinic of the National Medical Research Center for Therapy and Preventive Medicine (Moscow, Russia), receiving PCSK9 inhibitor and having lipid profile in dynamics, was carried out (n=77). Cardiovascular risk (CVR) and low-density lipoprotein cholesterol (LDL-C) target levels were evaluated in accordance with the Russian guidelines for the diagnostics and correction of dyslipidemias 2020.Results. Of 77 patients taking PCSK9 inhibitors (44.2% males, the median of age 56 [47; 66] years), the majority (64.0%) had a probable or definite familial hypercholesterolemia (FH). The proportion of other lipid metabolism disorders, pure hypercholesterolemia and combined hyperlipidemia was 21% and 15%. More than half of the patients (68.8%) had a very high CVR, mainly due to the presence of coronary heart disease (84.9%). The proportion of patients receiving PCSK9 inhibitors as monotherapy was 7.8%, in combination with high-intensity statin therapy – 33.8%, as part of triple lipid-lowering therapy (high-intensity statin, ezetimibe, PCSK9 inhibitors) – 50.6%. Addition of PCSK9 inhibitors to combined lipid-lowering therapy enabled to reduce the LDL-C level to 1.02 [0.62; 1.39] mmol/l with its total decrease from the baseline by 87.3%. While taking PCSK9 inhibitors, LDL-C <1.8 mmol/l and <1.4 mmol/l achieved at 78.3% and 57.7% FH patients with high and very high CVR, respectively. Among patients with other hyperlipidemias, 74.1% of patients with very high CVR was achieved the target LDL-C level <1.4 mmol/l.Conclusion: In a specialized lipid center, PCSK9 inhibitors are prescribed to patients with high or very high CVR, most of whom are FH patients. The effectiveness of the use of PCSK9 inhibitors in real-world practice is comparable to the results of clinical trials.